Pemahaman Siswa Terhadap Materi Hormat Kepada Guru Hubungannya Dengan Akhlak Mereka Di Sekolah - Siti Sarah (Gunung Djati Conference Series, 2022)
This research is motivated by the lack of good morals of students at school even though in Islamic religious education subjects there are respectful learning materials for teachers that aim to make students imitate and imitate respect for anyone, especially teachers. It is interesting to study whether there is a relationship between students' understanding of the subject matter of respect for teachers and their morals at school. This study uses a quantitative approach and correlational methods. Respondents were 40 students of class VIII E SMPN 3 Cileunyi. Data collection techniques are observation, interviews, tests, questionnaires and documentation. Meanwhile, the data analysis uses partial analysis and correlation analysis. The results showed that: 1) The reality of students' understanding of respect for teachers was in the medium category with a score of 63.7 which was in the 60-69 interval. 2) The moral reality of class VIII students at SMPN 3 Cileunyi was categorized as good with a score of 4.09 which was at intervals of 3.40 – 4.19. 3) The reality of the relationship between students' understanding of the subject matter of respect for teachers and students' morals in class VIII SMPN 3 Cileunyi is categorized as very strong with a correlation coefficient of 2.58 which is in the interval 0.80 - 1,000. Regarding the results of the correlation significance test, tcount is greater than ttable (3.04 > 2.024). The proposed hypothesis is accepted, namely that there is a relationship between students' understanding of the subject matter of respect for teachers and morals in schools.